1993
DOI: 10.1038/ki.1993.316
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical distribution and quantification of crystal matrix protein

Abstract: The aim of this study was to determine the immunohistochemical distribution and quantification of crystal matrix protein (CMP). CMP, a 31 kDa glycoprotein, is the principal macromolecule found in calcium oxalate crystals generated in human urine, and is a potent inhibitor of crystal aggregation. A polyclonal rabbit anti-human CMP antibody was used to examine renal tissue by immunohistochemical techniques and light microscopy (N = 45). Twenty-five other human organs were similarly assessed. Quantification was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 36 publications
1
44
0
Order By: Relevance
“…Although this would suggest that, on a microglobulin. This is reinforced by immunohistochemical studies demonstrating that urinary PTF1 is present in the most molar basis, the inhibitory potency of PTF1 is almost eightfold that of nephrocalcin and more than double that of bikunin, it is lithogenic regions of the human nephron [40].…”
Section: With Itsmentioning
confidence: 73%
“…Although this would suggest that, on a microglobulin. This is reinforced by immunohistochemical studies demonstrating that urinary PTF1 is present in the most molar basis, the inhibitory potency of PTF1 is almost eightfold that of nephrocalcin and more than double that of bikunin, it is lithogenic regions of the human nephron [40].…”
Section: With Itsmentioning
confidence: 73%
“…Verkoelen and coworkers reported on nephrolithasisrelated proteins being synthesized in the kidney [30,31] . These proteins are also known for their role in wound healing [32,33] .…”
Section: Discussionmentioning
confidence: 99%
“…HMM forms (Ͼ40 kDa) are likely to be other PF1-containing activation peptides of prothrombin, primarily prothrombin fragment 1ϩ2, with a molecular mass of 43 kDa (40). Immunohistochemical analysis of human kidneys has shown that PF1 is synthesized in the proximity of renal stones and is more abundant in the kidneys of SF than in healthy individuals (41). However, to date no differences have been found in the relative amounts of any prothrombin forms in the urine of CaOx SF vs. normal controls (14).…”
Section: Discussionmentioning
confidence: 99%